Using an Index of Atmospheric Circulation for Long Range Forecasting of River Breakup (Ispolzovanie Indeksa Atmosfernoii Tsirkulyatsii dlya Razrabotki Dolgosrochnogo Prognoza Srokov Vskrytiya Rek) - Savchenkova,E. I. (1972)
In the report the type of atmospheric circulation in a specific month, expressed by a numerical characteristic, is used for making long range forecasts of breakup of river ice in the north-eastern part of the European territory of USSR. (Author) Draft trans. of Meteorologiya i Gidrologiya (USSR) v5 p34-37 1957.